High school learners’ perceptions of careers in the built environment sector - Itumeleng Dube; Sizile Makola; Pumeza Saliwe; Ramodungoane Tabane (African Journal of Career Development, 2023)
Background: The purpose of this study was to examine the perceptions of learners on careers in the built environment. The industry is confronted with a critical shortage of skilled workers, which significantly hampers its growth and labour productivity. This workforce scarcity mainly stems from a lack of effective strategies for recruiting and retaining learners in construction programmes.